A Comparative Study of Anxiety, Depression and Stress in Caregivers of Psychiatric Illness and Chronic Medical Illness in Multan - Shah, Syed Zawar Hussain; Tabassum, Ahmed Shoaib; Saeed, Noshaba (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess and compare stress, anxiety and depression in long term caregivers of psychiatric and medical patients. Study Design: Cross-sectional comparative study. Place and Duration of Study: Out-patient Departments of Medicine and Psychiatry, Combined Military Hospital Multan, from Jan 2016 to Mar 2017. Methodology: One hundred and two (102) caregivers were selected through consecutive sampling. Each participant was interviewed at Medical and Psychiatry Outpatient Departments. The interview involved socio-demographic variables. Depression, anxiety and stress were assessed by using DASS Scale. Results: In this study, 102 caregivers were enrolled. Most of the caregivers, 67 (65.7%), were cared on a long-term basis for more than two years, while 35 (34.3%) had a history of care for more than five years. The mean score on the depression subscale of the depression, anxiety and stress scale (DASS) for medical caregivers (n=52) was 13.15 ± 10.552 as compared to psychiatric caregivers (n=50) 19.14 ± 9.337 and this difference was statistically significant. The mean score on the anxiety subscale for medical caregivers compared to psychiatric caregivers was also statistically significant. The mean score on the stress subscale for medical caregivers (n=52) was 15.58 ± 10.03 as compared to psychiatric caregivers (n=50) caregivers 20.38 ± 8.20, and this difference (20.38 vs 15.58, p=0.009) was statistically significant. Conclusion: This study suggested a clinically significant relationship between anxiety, depression, and stress with caregiving experience. There is a higher level of depression, anxiety and stress in caregivers of psychiatric patients than in caregivers of medical illnesses.